The case of the summer camp caper - Katschke, Judy (HarperEntertainment New York, NY, 1999)
When Mary-Kate and Ashley go away to camp, someone tries to frame Mary-Kate for a series of thefts, and she must rely on her sister Ashley to clear her of the blame